Interior Department Appropriation Bill for 1950. hearings before the United States Senate Committee on Appropriations, Eighty-First Congress, first session, on May 23, 26, 27, 30, 31, June 1-4, 6, 7, 1949. (U.S. Congressional Hearings., 1949)
Considers (81) H.R. 3838.